Pharmacovigilance in Portugal: Activity of the Central Pharmacovigilance Unit - Batel-Marques, Francisco (2015)
Introduction: The aim of this study was to characterize the spontaneous reports of adverse events that were received by the Central Portugal Regional Pharmacovigilance Unit.Material and Methods: Spontaneous reports received between 01/2001 and 12/2013 were considered. The annual reporting ratios were estimated. The cases were characterized according to their seriousness, previous description, causality assessment, origin and professional group of the reporter, type of adverse event and pharmacotherapeutic groups of the suspected drugs most frequently reported.Results: The Pharmacovigilance Unit received 2408 reports that contained 5749 adverse events. In 2013, the reporting rate was estimated at 171 reports per million inhabitants. Fifty-five percent of the reports were assessed as serious. Ninety percent of the cases were assessed as being at least possibly related with the suspected drug. The suspected drugs most frequently reported were antiinfectives for systemic use (n = 809, 33%). The most frequently reported adverse events were “Skin and subcutaneous tissue disorders” (n = 1139, 20%). There were 154 (6.4%) reports resulting in life-threatening situations and/or death, and 88 (3.6%) containing at least one adverse event assessed as serious, unknown and certain or probable.Discussion: The present results are in line with those found in other studies, namely the seriousness and type of the adverse eventsand the pharmacotherapeutic groups of the most frequently reported suspected drugs.Conclusion: In the last years, the Central Portugal Regional Pharmacovigilance Unit has registered a growth in the reporting rate in general, as well as an increase in the reporting of unknown and serious adverse drug reactions.